Consequences of Employees’ Perception towards their Jobs: Evidence from the Leather Industry of Bangladesh - Kamal, Md Aktar; Anik, Rakib Hasan (Asian Journal of Empirical Research, 2019)
The study is an attempt to explore the employees’ perception towards incentives and benefits plans in the leather industry of Bangladesh. Moreover, it also aims to know the behavior of the supervisors towards workers, besides their health and safety measures along with their family’s living conditions and above all, the standards and status of working life of the employees. Based on the two-stage analytical procedures, the researchers intend to investigate the measurement model and the structural model. Further, in order to investigate the significance of a path coefficient and the loading aspect, the bootstrapping method has been used for this study. This study significantly proved that health and safety measures, as well as salary and benefits at the workplace, have had a positive significant impact on job satisfaction and employees’ retention. However, the current study failed to prove that supervisor’s behavior and conditions of work and family life had a significant impact on job satisfaction and employees’ retention.